Selective extraction and stabilization of bioactive compounds from rosemary leaves using a biphasic NADES - Vieira, Carolina; Rebocho, Sílvia; Craveiro, Rita; Paiva, Alexandre; Duarte, Ana Rita C. (Frontiers in Chemistry, 2022)
Rosemary (Rosmarinus officinalis) is a natural source of bioactive compounds with high antioxidant activity. It has been used since ancient times as a medicinal herb, and currently is widely used due to its inherent pharmacological and therapeutic potential, in pharmaceutical, food, and cosmetic industries. Recently, natural deep eutectic systems (NADES) have been considered as suitable extraction solvents for bioactive compounds, with high solvent power, low toxicity, biodegradability, and low environmental impact. The present work concerns the extraction of compounds such as rosmarinic acid, carnosol, carnosic acid and caffeic acid, from rosemary using NADES. The extraction was carried out using two methods, heat and stirring (HS) and ultrasound assisted extraction (UAE). The NADES composed by menthol and lauric acid at a molar ratio of 2 to 1 - Me:Lau (2:1) -, extracted preferentially carnosic acid and carnosol, showing that this NADES exhibits selectivity for nonpolar compounds. On the other hand, the system Lactic acid: glucose (LA:Glu (5:1)) extracted preferentially rosmaniric acid, which is a more polar compound. Taking advantage the different polarities of these NADES, a simultaneous extraction was carried out, where the two NADES form a biphasic system. The system LA:Glu (5:1)/Men:Lau (2:1) presented the most promising results, reaching 1.00±0.12 mg of rosmarinic acid/g rosemary and 0.26±0.04 mg caffeic acid/g rosemary in the more polar phase, and 2.30±0.18 mg of carnosol/g of rosemary and 17.54±1.88 mg carnosic acid/g rosemary in the nonpolar phase. This work reveals that is possible to use at the same time two different systems and extract different compounds in a single step process, under the same conditions. NADES are also reported to stabilize bioactive compounds, due to their interactions established with NADES components. To determine the extracts stability with time, the compounds of interest were quantified by HPLC at different time points. This allowed to conclude that bioactive compounds from rosemary were stable in NADES for long periods of time, in particularly carnosic acid presented only a decrease of 25% in its antioxidant activity after three months, whereas the carnosic acid extracted and kept in methanol was no longer detected after 15 days.